2009
DOI: 10.1345/aph.1m086
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Assessment and Counseling Provided with the Supply of Nonprescription Asthma Reliever Medication: A Simulated Patient Study

Abstract: Both patient assessment and medication counseling were suboptimal compared with recommended practice when nonprescription asthma reliever medication was supplied in the community pharmacy setting. Pharmacy and pharmacist demographic variables do not appear to affect assessment of asthma control. This research indicates the need for substantial improvements in practice in order to provide reliever medication in line with Quality Use of Medication principles of ensuring safe and effective use of medication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
63
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(71 citation statements)
references
References 22 publications
7
63
0
Order By: Relevance
“…Pharmacy assistants had no knowledge of the SABA guidelines but articulated being highly involved in the provision of nonprescription asthma reliever medications and in some cases saw it as "their responsibility". This is consistent with prior research in this region that observed in 47 % of non-prescription sales of beta-agonists there was no obvious involvement of a pharmacist [7]. The participation of pharmacy assistants is despite the current legislative requirements for direct pharmacist involvement and despite the fact they are not qualified or trained to undertake this role.…”
Section: Discussionsupporting
confidence: 89%
“…Pharmacy assistants had no knowledge of the SABA guidelines but articulated being highly involved in the provision of nonprescription asthma reliever medications and in some cases saw it as "their responsibility". This is consistent with prior research in this region that observed in 47 % of non-prescription sales of beta-agonists there was no obvious involvement of a pharmacist [7]. The participation of pharmacy assistants is despite the current legislative requirements for direct pharmacist involvement and despite the fact they are not qualified or trained to undertake this role.…”
Section: Discussionsupporting
confidence: 89%
“…Schneider and colleagues showed a correlation between questioning and appropriate outcome in a mystery shopping study involving a request for salbutamol for asthma. 27 Watson and colleagues also found a similar correlation when examining the supply of non-prescription antifungals for vaginal thrush. 28 Collins and colleagues also showed a correlation between appropriate referral to a medical practitioner and the number of questions asked.…”
Section: Discussionmentioning
confidence: 75%
“…In a study carried out in the United States that evaluated a pharmacist's practice in patient education when dispensing an MDI to an investigator posing as a patient, only 13% of pharmacists offered initially to provide information regarding correct technique, and when asked for instruction on MDI usage, 53% of pharmacists offered information [42]. Also, in a simulated patient study performed in 160 Australian community pharmacies in 2009, only 24% of pharmacists provided counseling on inhalation technique [43]. Furthermore, in a recent survey in a sample of 77 Australian community pharmacists, 54% reported that they demonstrated the inhalation technique for new inhaled medicines and 35% checked for written asthma self-management plan possession.…”
Section: Discussionmentioning
confidence: 99%